Analisis Pengaruh Faktor Harga Tiket, Fasilitas Rekreasi, Hiburan Music Live, Promosi Dan Pelayanan Terhadap Keputusan Berkunjung Ke Taman Rekreasi Oleng Sibuttong, Di Desa Biting, Arjasa, Jember Pada Tahun Baru 2017 (Tanggal 1-1-2017) - Eko Raharjanto (Yos Soedarso Economic Journal (YEJ), 2019)
ANALYSIS OF THE INFLUENCE OF THE TICKET PRICE, RECREATION FACILITIES, LIVE MUSIC ENTERTAINMENT, PROMOTIONS AND SERVICES ON THE VISITTING DECISION TO OLENG SIBUTTONG RECREATION PARK, AT BITING VILLAGE, DISTRICT OF ARJASA, THE REGION OF JEMBER IN NEW YEAR 2017(DATE ON THE 1ST OF JANUARY 2017(Case study on  UMKM,a Tourism Micro Companies Unit in The Region of Jember)The purpose of the research is to study  whether TheTicket Price, RecreationFasilities, Live Music Entertainment, Promotion and Services  influence visitting decision.The research was conducted on the people of Jember that visit Oleng Sibuttong Recreation Park in the new year 2017 (the date on the 1st  of January 2017) . Data was collected using questionnaires, sampling using purposive sampling where researcher have certain criterias corresponding research purposes. Samples were taken of 40 people.                                                     It can be suggested that the company should pay more attention to the ticket price. With the result that the better price ticket can increase the visitting decisions of visitors. In addition the company also must maintain and provide receation fasilities because the better fasilities will make the visitting decision increased and in addition the company also must provide live music entertainment because the attractive live music entertainment will make the visitting decision increased. Furthermore vigorous campain conducted by Oleng Sibuttong Recreation Park and services also effect the visitting decision. Here the company suggested to create interesting promotions and advertisements as well as easy to remember and improve services getting better. Especially in the holliday such as in the happy new year the company must improve the music live entertainment and so the promotion as well, because these variables are very significant and dominan on desicion of visitting of Jember society at Oleng Sibuttong Recreation Park. Keyword :Ticket Price, Recreation fasilities, Live music entertainment, Promotion, Services and visitting decision